Konkordaty podpisane z państwami Ameryki Łacińskiej do końca XIX w. - Osuchowska, Marta (Kwartalnik Prawa Publicznego, 2014)
The most important agreement regulating relations between a State and the Catholic Church is a concordat. This bilateral international treaty is specific due to the fact that one of the parties is the Holy See. From the times of Restoration to the late 19th century, the Holy See established diplomatic relations with Latin American countries and signed concordats with them. During the pontificates of Pius IX and Leo XIII, the Holy See signed many concordats. These agreements were well prepared, analyzed and strengthen the position of this religious association in Latin American states yet having well established place. Several among them were a subject of analysis and stand out from the others. This allowed to identify areas of direct influence of the Catholic Church and determine effects of this impact that are seen in this countries to this day.